Levantamento de doenças da alface e da couve em produção urbana de Lavras (MG) e Campina Grande (PB) - Silva, Kercio Estevam da (2015)
Urban agriculture has great potential for vegetable production in Brazil. Kale and lettuce are the most commonly planted crops but little is yet know about the impact of plant disease under these production systems. In this study, we aimed to survey the diseases occurring on lettuce and kale and establish the relationship to crop management practices adopted by growers from two different regions. During one year for each location (Lavras and Campina Grande), weekly assessments were carried out on individual farmholders per location. From individual disease ratings, the areas under the disease progress curves (AUDPC) were calculated and means compared (Kruskal-Wallis test). According to results, the downy mildew of lettuce in Lavras was the most important disease with higher AUDPC during winter, while septoria leaf spot was important only for farmers that relied exclusively on hose irrigation of plants. For kale, black rot was the most important disease, however, AUDPC was lower for growers that used straw mulch. That adopted technique also reduced powdery mildew AUDPC. In Campina Grande, the cercospora leaf spot and septoria leaf spot of lettuce were the most important diseases. Regarding the growing season, there were no differences for severity of cercospora leaf spot. However, the winter and fall were the conditions the most increased septoria leaf spot AUDPC. Powdery mildew and black rot were the most important diseases occurring on kale. Powdery mildew greatest AUDPC was recorded in winter and fall and for growers that used cattle manure. The cercospora leaf spot and septoria leaf spot of lettuce were the major diseases in Campina Grande, while the downy mildew and septoria leaf spot of lettuce were the major disease in Lavras. Regardless of the region, the major diseases were powdery mildew and black rot for kale. Therefore, the growing season and crop management practices influenced the importance of the disease of both lettuce and kale in urban agriculture growers and solutions for the diseases management may be found within the own growers communities.